Neobanks’ Footprint on the Transformative Path of the Austrian and the Slovenian Banking Market - Veršič, Sabina; Wirth, Martin; Jagrič, Timotej; Jagrič, Vita (Naše gospodarstvo/Our economy, 2025)
The digital transformation in banking, which is supported by the European regulatory framework, has enabled new business models for banking. One example of these changes is the emergence of neobanks. We examine the presence of neobanks in two national markets, Austria and Slovenia. Despite the geographical proximity and rich history of banking integration between the two markets, our findings reveal significant differences in this perspective between the two markets. In the analytical part, we use available indirect and descriptive data. We have identified two historical periods. In the first, domestic neobanks appeared. Unlike in Austria, where there is a rich history of domestic neobanks, there were none in Slovenia. In the second identified period, the most propulsive European neobanks are similarly active in both markets, which increases competition in the banking markets. In the future, the neobanks could contribute to the increase in the mobility of deposits outside the national banking markets.